Comprehensive in situ mapping of human cortical transcriptomic cell types - Christoffer Mattsson Langseth (Nature Portfolio, 2021)
Langseth et al. present cell type maps of human cortical tissue sections and show an efficient and robust workflow to accurately resolve anatomical organization of human brain tissue.